Penerapan Teknologi Reproduksi Sapi Potong pada Peternakan Rakyat Kelompok Tani Makmur Sejahtera: Implementation of Reproductive Technology in Beef Cattle Farming at the Makmur Sejahtera Farmers' Group - Hasrin, Hasrin; Zulkharnaim, Zulkharnaim; Hasman, Hasman; Syamsuddin, Syamsuddin; Wulandari, Sri Helda; Sari, Anggun Permata; Nurhidayah, Asmaul Fitriana; Walinono, Andi Muh. Fuad Al Kautsar; Diansyah, Athhar Manabi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
One of the efforts to increase the calving rate in cattle is by applying artificial insemination guns. The main issue currently faced by the partners is the lack of implementation of artificial insemination guns and veterinary personnel, resulting in a low birth rate. The methods used in this community service program include focus group discussions and training on artificial insemination technology, animal health management, as well as livestock fattening, and feed processing based on local raw materials for pregnant cows. The outcome of this activity is reflected in the increased knowledge of the "Makmur Sejahtera" farmer group in Teluk Kampe Village, and the motivation to apply beef cattle reproductive technology, as analyzed through pre-test and post-test results. The implementation of beef cattle reproductive technology is expected to help improve productivity and boost the economy of the partners or members of the "Makmur Sejahtera" farmer group if applied effectively.